PENERAPAN EDUCATION MANAGEMENT INFORMATION SYSTEM (EMIS) DI LEMBAGA PENDIDIKAN KEAGAMAAN DAN PONDOK PESANTREN PADA KANTOR KEMENTERIAN AGAMA KOTA MAKASSAR - Rasdiana Sina; Fatmawati Fatmawati; Abdul Mahsyar (JPPM: Journal of Public Policy and Management, 2019)
This study aimed to determine the implementation of the Education Management Information System (EMIS) at the Islamic boarding schools of Makassar Ministry of Religion Affairs. This research was a qualitative research. The data collection techniques were conducted by observation, in-depth interviews, and documentation. This research consisted of 4 indicators, namely the human resources component by measuring internal factors consisting of attitude, skill, and knowledge, which the three benchmarks were sufficiently fulfilled. The human resources external factors with the first indicator of work tools had not been maximized.; the second, the  supporting work resources included adequate funds and supporting infrastructure; the third was coworkers which were sufficiently well to be implemented.The hardware resources componets were still found to be not fully supportive and adequate. The software resources components, in terms of processes and computer programs that support EMIS, were sufficiently well implemented. Data resources in the implementation of EMIS were seen from 3 sub indicators, namely the data category, the timeliness of data collection, and the rules in the data collection process where the three elements were sufficiently well conducted by the EMIS operators. Supporting factors that support the implementation of EMIS consisted of the first, the role of the leaders by coordinating activities was sufficiently well implemented. Second, understanding of the EMIS program, the operators of the institution were sufficiently understood about EMIS inhibiting factors. The financing component had not been managed properly which had resulted in the existing funds not being used optimally to support the EMIS. Whereas in terms of operator quality, it can be seen from two elements, namely training and disciplinary institutions that were not yet sufficiently supportive, so that there was a need for improvements in education and training for EMIS operators in institutions, as well as in the discipline of institutions in presenting data collection results.